The Artsakh Problem in Modern Geopolitical and Regional Developments - Khachatrian, Artak (History and Culture, 2022)
The Artsakh movement started during the collapse of the Soviet Union, and the subsequent armed conflict raised it to a new level. With the establishment of the OSCE Minsk Group, the conflict was internationalized, the further development and transformations of which were able to change the perceptions and way of the South Caucasus. The article discusses the main targets of the policy of Azerbaijan, their far-reaching goals, and, accordingly, regional geopolitical transformations. Azerbaijan has continuously pursued a targeted economic, demographic, administrative-political policy since the Soviet period, the aim of which was the removal of the Armenian element from Nagorno-Karabakh, the gradual absorption of the territory in terms of culture and territory. This policy was implemented in the Soviet period and continued in the post-Soviet period. And in 2020, as a result of the 44-day war in September-November, the South Caucasus is less perceived as the post-Soviet region. There are attempts to consider it a part of the Middle East region. Following the collapse of the Soviet Union by the Soviet tradition, the South Caucasus, among other regions, continued to be viewed as a zone of Russian influence. After the military phase of the conflict, the reduction of Russia’s sole influence in the region has led to the activation of Turkey and the possibility of a further role.